Psychological peqularities of behaviour of a person with various addictions - Pasichnyk, Lesia (Psychological Prospects Journal, 2024)
The purpose of the article is to carry out a theoretical analysis of scientific sources on the study of psychological characteristics of behaviour of a person with various addictions. Methods. The article uses the methods of theoretical study of scientific literature: analysis, synthesis, abstraction, and generalisation. Results. A review of the theoretical and empirical basis of research on the psychological characteristics of addictive behaviour of individuals suggests that the problem of addictions is relevant, widely represented and studied by scientists in various aspects. There is an increase and thoroughness of scientific research on non-chemical (behavioural) addictions. Among Ukrainian researchers, the predominant topics are the study of psychological features of the formation of addictive behaviour in modern youth, the influence of the family on the formation of addictive behaviour, urge addiction and workaholism, psychological features of food addiction, Internet addiction, etc. Conclusions. The family system is the basis for the development of individual psychological factors of predisposition to addictive behaviour (attachment styles, the level of manifestation of character accentuations, resistance to emotional stress, etc.) Dependence on psychoactive substances is considered a complex and chronic condition. Due to the legalisation of cannabis products in a number of countries, its availability is increasing. Accessibility is one of the negative factors in the development of chemical dependence. The distinction between non-problematic behaviour and behavioural addiction (workaholism, overeating, internet addiction, gambling, etc.) in everyday life is very vague, and negative consequences for a person’s health and well-being can be an evidence of addiction. Signs of established addiction (chemical and non-chemical) are: impaired control over behaviour, prioritisation, continuation and escalation of behaviour despite negative consequences. Until recently, the tools for empirical research on addictive behaviour were mainly developed and improved for the study of substance dependence and were used to study all types of addictions, including behavioural ones. At the present level, there are two trends: the use of existing tools for the study of addictions; development and implementation of new methods for chemical (substance dependence) and non-chemical (behavioural) addictions.